Effect of replacement of fish meal with processed soybean on growth, digestibility and nutrient retention in Mugil cephalus (Linn.) fry - Kalla, Alok; Garg, S K; Kaushik, C P; Arasu, A R T; Dinodia, G S (Indian Journal of Fisheries, 2011)
Mugil cephalus fry were maintained in glass aquaria filled with inland salinegroundwater (15 ppt), and fed on one of the ten (1-10) isonitrogenous diets(energy contents 16.43 kJg-1 to 16.83 k Jg-1) formulated with and without supplementingmineral premix and amino acids (MPA). Fish meal was replacedwith equal proportion of hydrothermically processed full fat soybean (Glycinemax) at four inclusion levels (25, 50, 75 and 100 g kg-1 of diet). Growth performancewas evaluated by feeding the fish once only @ 5% BW d-1 maintainedunder laboratory conditions (LD 12:12 at 200C) for 70 days. Studies have revealedthat growth, per cent gain in body weight, specific growth rate (SGR % d-1), apparent protein digestibility (APD%), protein effeciency ratio (PER), grossprotein retention (GPR) and gross energy retention (GER) increased with increasein the inclusion levels of soybean (upto 75g kg-1 of diet) in comparisonwith the fish fed on control diet containing fish meal as the protein source.Carcass of such fish also had high contents of protein, fat and energy, whilethose of moisture and ash contents remained significantly (P